(untitled) (Journal of Science and Technology, 2016)
The occurrence of antibiotic-resistant bacteria in faeces of apparently healthy individual volunteers was investigated. Faecal samples were collected from 216 individuals comprising 138 adults (70 males and 68 females) and 78 children aged between 4 months and 42 years (mean age was 30.2 months). Individuals on antibiotics were excluded from the study. Faecal samples were examined microbiologically for the presence of bacteria resistant to commonly employed antibiotics. Three hundred and eleven bacterial isolates were recovered; the bacteria detected included Escherichia coli (16.6%), Enterobacter sp. (13.6%), Salmonella sp. (13.2%), Proteus sp. (12.6%), Serratia sp. (11.9%), Klebsiella sp. (9.3%) and Citrobacter sp. (7.9%). Others included Hafnia sp. (3.6%), Providencia sp. (3.0%), Shigella sp. (3.0%), Edwardsiella sp. (2.6%), Yersinia sp. (2.0%) and Pseudomonas sp. (0.7%). Overall resistance to antibiotics was generally high; resistance to streptomycin (59.0%) was highest, while it was least to gentamicin (39.5%). High proportion (96%) of the isolates showed multiple antibiotic resistance (MAR) with 151 phenotypes.